10.1146/annurev-nutr-072610-145121 (CrossRef Listing of Deleted DOIs, 2000)
Time-restricted feeding (TRF), which confines food intake to a defined daily window, has emerged as a promising nonpharmacological strategy to improve health by aligning behavior and physiology with the endogenous circadian clock. Preclinical research has expanded substantially, now spanning both nocturnal and diurnal species, diverse dietary regimens, varying intervention durations, and examinations of sex-specific responses. These consistently show that synchronizing feeding-fasting cycles with the natural active phase of an organism's circadian rhythm enhances rhythmic gene expression across tissues. Concomitantly, this mitigates metabolic dysfunction, reduces inflammation, and lowers disease risk, often without reducing caloric intake. While findings in animal models are robust, human outcomes have been more modest and variable, influenced by the timing and duration of feeding window, metabolic state, and sex. This review synthesizes current insights into the relationship between TRF and circadian rhythms, highlighting recent discoveries and the challenges that remain for translation to humans.